The Effectiveness of TPS and STAD Models Against Skills Writing Fantasy Texts Reviewed from Motivation Study Grade VII Junior High School Students - Hastuti, Choirul Imsa; Suryaman, Maman (East Asian Journal of Multidisciplinary Research, 2024)
Study This aiming for know the effectiveness of the TPS and STAD models in learning write text fantasy If reviewed from motivation Study student class VII. This research is a quantitative research . The population in this study was S MPN 7 Magelang. The sample in this study used the cluster random sampling technique . The data in this study were the scores of the results of the fantasy text writing skills test and the scores of the learning motivation questionnaire. Data analysis used the anova test and the difference test . The results of the study This show There is a significant difference in the ability to write fantasy texts between grade VII students before and after using the STAD and TPS models in learning write text fantasy , as well as the STAD model more effective compared to with the TPS model in learning write text fantasy If reviewed from motivation Study